Pengembangan Aplikasi Pembelajaran Berbasis Macromedia Flash Untuk Pembelajaran Membaca Dan Menulis Aksara Jawa Di Sekolah Dasar - Rio Ariadi; Dwi Kameluh Agustina; Sripit Widiastuti (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
This application for learning to read and write Javanese script was developed using the Macromedia Flash application. This learning application was developed from previous research to make it easier for students to learn to read and write Javanese script. This research uses a Design and Development (D&D) research design because the stages used only reach the validation stage, namely problem analysis, product design, and product validation. Problem analysis is carried out to find out which media suits the problems that occur in elementary schools. After that, the media design process is carried out starting from the appearance to the running process of the media until the initial media is produced. The initial media is then validated by media experts and material experts to obtain media that is truly suitable for use in learning Javanese script. The assessment results by media experts were 79.17% (feasible) and by material experts were 86.67% (very feasible).